The Effectiveness of Inquiry-Based Learning in Enhancing Student Creativity as a Dimension of Deep Learning and Its Impact on Learning Outcomes in Elementary Education - Ariyatun,; Suriswo,; Apriani, Dewi (Jurnal Paedagogy, 2026)
This study aims to investigate the effectiveness of inquiry-based learning in enhancing students’ creativity as a dimension of deep learning and its impact on learning outcomes in elementary education. The research was conducted with sixth-grade students at SDN Wanamulya, Pemalang Regency. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed. The instruments included a creativity observation checklist and an IPAS learning achievement test. Data were analyzed using descriptive statistics and comparative analysis to examine changes in students’ creativity and learning outcomes before and after the implementation of inquiry-based learning. The findings indicate that students’ creativity improved following the implementation of inquiry-based learning, as reflected in the increase in the mean creativity score from 2.34 in the pretest to 3.54 in the posttest. Improvements were observed across several dimensions, including idea fluency, flexibility in problem-solving, originality, and elaboration. In addition, students’ learning outcomes showed a significant increase, with the class average score rising from 63.40 in the pretest to 82.15 in the posttest. The percentage of students achieving the minimum mastery criterion also increased from 45% to 85%. In conclusion, inquiry-based learning is effective in promoting meaningful learning and supporting deep learning by enhancing students’ creativity and improving learning outcomes in elementary education.